The Issue of Exoneration For the Scholar Haji Mulla Muhammad al-Bukani - al-Jalali Famous for Mulla Muhammad al-Rais - كريم حسين حسن (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This research concentrates on the spouse clearance, which means the wife forgives her husband from all the rights when it comes to divorce. This issue in Islamic Fiqh is called (Al-Ebrah) clearance. A well-known Kurdish Expert Haji Mula Mohammed Bokani known as Raays, who was also Mula and the teacher of Galalla Village in Sharbajeer district, wrote about this subject relying on the significant sources of Islamic Fiqh, especially Imam Al-Shaffi’y theory, who is an inventor in this issue. All the phrases and words that are classified between the wife and the husband would be different and change based on their rules regarding the divorce between them. For instance, according to the Islamic jurisprudence, some of those words and phrases considered as a (khwl’) which means divorce because of something like for money or something else. Also, some of them considered as (ta’liq) which means the husband have conditions for his wife, if she does them, she is not his wife anymore. The third one consists as (raj’i). These are all well described in the jurisprudence books. The writer explained all of them with their specific rules, and all his descriptions are based on evidence and reliable sources. The researcher has rectified a pamphlet which contains all of the Ayaa, al hadith, and scientists saying. In case if the re-writer of the pamphlet made a mistake, he showed it in between [ ] and analyze it at the footer. Any word or phrases is ambiguous and not straightforward in case of meaning, he explained it very well in a very scientific way based on evidence and research.